Economic support online-technology: a comparison between China and Indonesia - Pranolo, Andri; Nuryana, Zalik; Sularso, Sularso; Fadillah, Dani (Association for Scientific Computing Electrical and Engineering, 2023)
Following the United States, China is the world's second-biggest economy and the world's largest exporter of goods. Chinese and Indonesian economies differ significantly in terms of development and implementation and the availability of technology and transportation to support them, particularly in terms of GDP value and other indicators of economic health. The topography and climate of China and Indonesia are covered in detail in this study, as is the economic relationship between China and Indonesia, covered in the second section. According to the economic viewpoints, the economic topic incorporates technology and transportation. Both countries must improve their cooperation to reap mutual benefits in the future.